Obstacles and Successes in Learning Vocabulary from Context - Zuraina, Ali; Ahmad Fauzi, Mohd Ayub (2012)
This study examines the use of context method in learning vocabulary among students at tertiary level. The participants were 43 first-year undergraduate students from one of the technical universities in Malaysia. The vocabulary pre-test and post-test as well semistructured interviews were used as the main methods for the data collection. Results from the t-test showed that there was an improvement in guessing meaning from context among the students before and after they were taught using the method. However, competent learners stand to benefit from the method better than the basic learners when sentences using the target words were distributed to them. The target words in the study were selected from the Tell Me More software and only 42 words were used for the study. Consideration of the use of context method in learning vocabulary suggests that teachers need to train the students the method in early semester as it will help the latter in developing ways to deal with unknown vocabulary. This study is perhaps one of the first to use sentences illustrating the target words while other studies use reading texts as the resources in teaching students the context method.